2022
DOI: 10.1111/are.15802
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and SNPs association with growth‐related traits of myosin heavy chains from the pearl oyster Pinctada fucata martensii

Abstract: Myosin heavy chains (MYHs) are important proteins in muscle growth and contraction, which may potentially enhance shellfish growth. In this study, the MYH gene from Pinctada fucata martensii (PmMYH) was studied. Sequence analysis revealed that it has an open reading frame of 5823 bp that encode 1940 polypeptide residues. Analysis of PmMYH showed four conserved domains, namely Myosin_N, MYSc, IQ and Myosin_tail_1. Blast analysis confirmed that PmMYH has a high identity with MYH protein sequences from Crassostre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…European green crab Carcinus maenas is invasive on the Pacific coasts of North America and has been found to have some SNPs linked to a chromosomal inversion associated with latitude and winter temperature [ 218 ]. In the studies of myosin heavy-chain proteins important for the muscle growth gene MYH in Pinctada fucata martensii had 18 out of 95 SNPs discovered in the exons region, were significantly associated with growth, of which 2 were confirmed in 2 populations [ 219 ]. In the studies of newly established populations of the marine snail Nerita yoldii north of the Yangtze River estuary, neutral SNPs confirmed that it consisted of founders and was distinct from the southern source population [ 220 ].…”
Section: Selection and Adaptation Of Aquatic Populations To Environme...mentioning
confidence: 99%
“…European green crab Carcinus maenas is invasive on the Pacific coasts of North America and has been found to have some SNPs linked to a chromosomal inversion associated with latitude and winter temperature [ 218 ]. In the studies of myosin heavy-chain proteins important for the muscle growth gene MYH in Pinctada fucata martensii had 18 out of 95 SNPs discovered in the exons region, were significantly associated with growth, of which 2 were confirmed in 2 populations [ 219 ]. In the studies of newly established populations of the marine snail Nerita yoldii north of the Yangtze River estuary, neutral SNPs confirmed that it consisted of founders and was distinct from the southern source population [ 220 ].…”
Section: Selection and Adaptation Of Aquatic Populations To Environme...mentioning
confidence: 99%
“…Quantitative real-time RT-PCR (qRT-PCR) was performed with b-actin as the reference gene to determine mRNA expression. Research has showed that b-actin was the most stable reference gene for different tissues and different embryonic developmental stages (Wang and He, 2013) and have been widely used as reference genes for qRT-PCR analysis (Wang et al, 2019;Lai et al, 2021;Chen et al, 2022). qRT-PCR was performed with SYBR Green Master Mix (Thermo-Fisher Scientific, USA) according to the protocol recommended by the manufacturer.…”
Section: Analysis Of Pm5-htr2 and Pm5-htr4 Expressionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) are important molecular markers that are located within trait-related genes and exhibit multiple superiorities for the identifcation of markers associated with target trait [13][14][15][16]. SNPs have been widely used in the genetic analysis of economic traits and hold multiple advantages over traditional microsatellite markers, including more accurate genotyping [17], fewer null alleles [18], greater selective efciency, the potential for quantitative trait loci (QTL) detection [19,20], being more adaptable to automation genotyping, and the ability to reveal hidden polymorphisms [21].…”
Section: Introductionmentioning
confidence: 99%